Combined effects of motor response, sensory modality, and stimulus intensity on temporal reproduction - Indraccolo, A; Spence, C; Vatakis, A; Harrar, V (Springer Berlin Heidelberg, 2015)
The ability to estimate a filled interval of time is affected by numerous non-temporal factors, such as the sensory modality, duration, and the intensity of the stimulus. Here we explore the role of modality (auditory or visual), stimulus intensity (low vs. high), and motor response speed on the ability to reproduce the duration of short (<1 s) filled intervals. In accordance with the literature, the reproduced duration was affected by both the modality and the intensity of the stimulus; longer reproduction times were generally observed for visual as compared to auditory stimuli, and for low as compared to high-intensity stimuli. We used general estimating equations in order to determine whether these factors independently affected participants' ability to reproduce a given duration, after eliminating the variability associated with reaction time, since it covaried with the reproduced durations. This analysis revealed that stimulus duration, modality, and intensity were all significant independent predictors of the reproduced durations. Additionally, duration interacted with intensity when reproducing auditory intervals. That is, after taking into account the general speeding-up effect that high-intensity stimuli have on responses, they seem to have an additional effect on the rate of the internal clock. These results support previous evidence suggesting that auditory and visual clocks run at different speeds.